Pulp Vitality Preservation of an Involved Tooth in a Large Radicular Cyst: A Case Report with 4-Year Recall - Asgary , Saeed; Parhizkar , Ardavan (Iranian Endodontic Journal, 2023)
The current case study presents the surgical endodontic retreatment of a central incisor with a large periapical cyst that had extended to the adjacent lateral incisor. After anaesthesia, a full mucoperiosteal flap was carefully incised and completely reflected. Then, the cyst was cautiously excised without performing curettage of the apical region of the adjacent tooth. A 3-mm deep root-end cavity on tooth #21 was prepared, filled and sealed with calcium-enriched mixture cement. At 6-month and 4-year follow-ups, tooth #21 was fully functional and exhibited no clinical signs/symptoms, and complete periapical healing was evident. This report indicates the importance of proper diagnosis as well as a careful surgical approach in the successful management of comparable cases without the overtreatment of involved teeth.